2018
DOI: 10.1007/s40641-018-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

Climate Feedback on Aerosol Emission and Atmospheric Concentrations

Abstract: Purpose of Review Climate factors may considerably impact on natural aerosol emissions and atmospheric distributions. The interdependencies of processes within the aerosol-climate system may thus cause climate feedbacks that need to be understood. Recent findings on various major climate impacts on aerosol distributions are summarized in this review. Recent Findings While generally atmospheric aerosol distributions are influenced by changes in precipitation, atmospheric mixing, and ventilation due to circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…While differences in sea salt account for less than 30% of the difference between CM4 and ESM4 (Dunne et al, ) at TCR (2.05 and 1.63 K, respectively) and ECS (5 and 3.1K, respectively), this study provides further support for the importance of reducing uncertainties in natural emissions and their response to temperature (Carslaw et al, ; Tegen & Schepanski, ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…While differences in sea salt account for less than 30% of the difference between CM4 and ESM4 (Dunne et al, ) at TCR (2.05 and 1.63 K, respectively) and ECS (5 and 3.1K, respectively), this study provides further support for the importance of reducing uncertainties in natural emissions and their response to temperature (Carslaw et al, ; Tegen & Schepanski, ).…”
Section: Discussionsupporting
confidence: 61%
“…Most model studies to date have found little change in global sea salt emissions in response to large climate perturbations, suggesting that sea salt may not be a significant climate feedback. This has been attributed to the weak response of surface oceanic wind speed, the primary driver of sea salt emissions, to climate change (Tegen & Schepanski, ). In particular, sea salt emissions were found to change little relative to present day ( <5%) under conditions representative of the last Glacial Maximum and in a doubled‐ normalCO2 climate (Mahowald et al, ; Yue et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, dust aerosol is one of the uncertainties the estimating aerosol climate feedbacks and the global energy budget in general. Whereas the emission of industrial aerosols becomes more and more controlled and regulated by political efforts [146], the emission of natural aerosols such as mineral dust is highly susceptible to modifications due to climate change thus showing a high potential for important feedbacks on the climate system [1] and vice versa [147]. Eventually, as anthropogenic aerosol emissions are expected to decline, this will lead to an increased contribution by natural aerosols to the global aerosol burden.…”
Section: Future Researchmentioning
confidence: 99%
“…Changing climate conditions that affect winds, the hydrological cycle and vegetation will affect aerosol emissions [25]. This is of interest for future climate change, where non-fossil fuel aerosol emissions can change along with direct anthropogenic emissions [26,27], and it is relevant for the attribution of changes in the framework of the Intergovernmental Panel on Climate Change (IPCC).…”
Section: Introductionmentioning
confidence: 99%